Spatial market integration: A case study of the Polish-Czech milk market - Monika Roman; Zdeňka Žáková Kroupová (Economies, 2022)
Analyses of spatial market integration contributes to the knowledge about market efficiency and provides information to policymakers, as the spatial integration of markets contributes to competitiveness and economic development. Although the integration of agri-food markets is widely discussed in the economic literature, research on the dairy sector is relatively limited. This paper fulfils the research gap with an in-depth investigation of spatial milk and dairy product market integration between two neighboring countries—Poland and Czechia—using regional data, and including both production and processing levels. The econometric analysis of time series covering the period 2001–2021 reveals that only long-run milk and skimmed milk powder (SMP) price relationships are between the Czech Republic and Poland. The results of the study confirm that the factors influencing spatial price relationships between the Czech Republic and Poland are: strong trade ties, the common moment of accession to the EU, a close distance between markets, and region specialization.
Keywords: 330; cointegration; Czechia; dairy products; market; milk; Poland; spatial integration